2019
DOI: 10.3390/w11030422
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Flow-Dependent Controllers for Remote Real-Time Pressure Control in a Water Distribution System with Stochastic Consumption

Abstract: The control of pressure at a remote critical node using a pressure control valve is a highly effective way to attain pressure management. To perform real-time control, various kinds of controllers can be used, including flow-dependent controllers. These controllers calculate valve setting adjustment based both on the deviation of the pressure from the set-point and on the flow rate at the valve site. After putting all the flow-dependent controllers present in the scientific literature within the same framework… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…The authors tested the dynamic response of their remotely-controlled valve to activation of a hydrant but, due to a long control time step and small gain warranting stability at that particular case, the system was unable to maintain adequate pressure levels and pressure variations up to 10m were observed. Similar conclusions were reiterated in Page and Creaco (2019) who reported instability at Δ ≤ 1min and found optimal behavior of their system at Δ = 3min. Galuppini et al (2019) used a sampling time of 1s but then concluded that longer sampling intervals might be preferable.…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…The authors tested the dynamic response of their remotely-controlled valve to activation of a hydrant but, due to a long control time step and small gain warranting stability at that particular case, the system was unable to maintain adequate pressure levels and pressure variations up to 10m were observed. Similar conclusions were reiterated in Page and Creaco (2019) who reported instability at Δ ≤ 1min and found optimal behavior of their system at Δ = 3min. Galuppini et al (2019) used a sampling time of 1s but then concluded that longer sampling intervals might be preferable.…”
Section: Introductionsupporting
confidence: 77%
“…The literature on RTC of WDNs is abundant and has recently been reviewed and summarized by Creaco et al (2019). The bulk of the publications on the subject are often based on static network models (Campisano et al 2010;Campisano et al 2012;Creaco and Franchini 2013;Campisano et al 2016;Giustolisi et al 2017;Page et al 2017b;Page et al 2017a;Creaco 2017;Page et al 2018;Berardi et al 2018;Page and Creaco 2019). The authors investigated reduction of leakage using different control strategies and controllers within an extended period simulation (EPS) environment where the implemented control algorithms would adjust the valve setting in between successive steady-state solutions.…”
Section: Introductionmentioning
confidence: 99%
“…In the work of [14], the authors presented an interesting application on real-time pressure control by analyzing different stochastic consumptions. As known, pressure management in water distribution systems is important to supply water in sufficient quantity and quality in a cost efficient and reliable way.…”
Section: Smart Real Time Control and Operationmentioning
confidence: 99%
“…Table A1 is shown as a function of the flow coefficient CV. Data are from references [23,24,[38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] or supplied by water utilities. Dotted lines are the average flow coefficient (vertical line) and the average dissipated power (horizontal line).…”
Section: Data Set Classification and Analysismentioning
confidence: 99%